“The Baby Became Horrible”: The Traumatized Adolescent Mother in Elizabeth Stuart Phelps’ 1870 Reforn Novel, Hedged In - D'amico, Luella (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
In her 1870 novel, Hedged In, Elizabeth Stuart Phelps explores the painful psychological underpinnings that social and historical constraints imposed on unwed adolescent mothers, interrogating the widespread belief that these fallen girls could never recover from their pasts. Through her character of abandoned and pregnant fifteen-year-old Nixy Trent, Phelps shows her middle-class audience the story of a young woman who overcomes her past and becomes an upstanding member of her community, transforming from unwed mother to respected teacher. Yet Nixy’s story isnot a resounding success: the youthful heroine suffers severe emotional trauma akin to that of contemporary sufferers of PTSD, and this essay argues that her mental illness ultimately kills her, eliminating the collective good that she otherwise could have offered those around her. Thus, Phelps suggests that social standards simply refusedto keep pace with the reform she felt the United States as a whole must undergo toaid teen mothers in their emotional healing processes. She further seems to hope that Nixy’s story would stir her readers to reconsider their ill treatment of these young women and thereby offer faith in these girls’ abilities to change rather than persistently chastising (and, in essence, retraumatizing) them for pasts that could never be erased.